Skeletal muscle derived Musclin protects the heart during pathological overload - Szaroszyk, Małgorzata; Kattih, Badder; Martin Garrido, Abel; Trogisch, Felix; Dittrich, Gesine M.; Grund, Andrea; Abouissa, Aya; Derlin, Katja; Meier, Martin; Holler, Tim; Korf, Mortimer; Völker, Katharina; et al. (Nature Communications, 2022)
Abstract - Cachexia is associated with poor prognosis in chronic heart failure patients, but the underlying mechanisms of cachexia triggered disease progression remain poorly understood. Here, we investigate whether the dysregulation of myokine expression from wasting skeletal muscle exaggerates heart failure. RNA sequencing from wasting skeletal muscles of mice with heart failure reveals a reduced expression of - Ostn - , which encodes the secreted myokine Musclin, previously implicated in the enhancement of natriuretic peptide signaling. By generating skeletal muscle specific - Ostn - knock-out and overexpressing mice, we demonstrate that reduced skeletal muscle Musclin levels exaggerate, while its overexpression in muscle attenuates cardiac dysfunction and myocardial fibrosis during pressure overload. Mechanistically, Musclin enhances the abundance of C-type natriuretic peptide (CNP), thereby promoting cardiomyocyte contractility through protein kinase A and inhibiting fibroblast activation through protein kinase G signaling. Because we also find reduced - OSTN - expression in skeletal muscle of heart failure patients, augmentation of Musclin might serve as therapeutic strategy.
Gesehen am 14.06.2023